Juridical Review of Minors Facing Legal Proceedings in Pornography Offenses - Lidya Imelda Rachmat; R. Rahaditya (Dinasti Research, 2024)
This research analyzes the legal perspective on children in conflict with the law in cases of pornography-related crimes. The primary focus of this study is on the implementation of Law No. 44 of 2008 on Pornography and the Juvenile Justice System in cases involving children as perpetrators or victims. The approach used combines normative and empirical studies with descriptive methods. The results indicate that although regulations are applied, there are challenges in field implementation, such as social stigma against children in conflict with the law. This study also highlights the importance of restorative justice approaches in handling these cases to minimize negative impacts on the child’s psychological and social development.